Direct Observation for Distinct Behaviors of Gamma-Ray Irradiation-Induced Subgap Density-of-States in Amorphous InGaZnO TFTs by Multiple-Wavelength Light Source - Yoo, Jaewook; Jo, Hyeun Seung; Jeon, Seung Bae; Moon, Taehwan; Lee, Hongseung; Lim, Seongbin; Song, Hyeonjun; Lee, Binhyeong; Yoon, Soon Joo; Kim, Soyeon; Park, Minah; Park, Seohyeon; et al. (Advanced Electronic Materials, 2024)
The amorphous In─Ga─Zn─O (a-IGZO) thin film transistors (TFTs) have attracted attention as a cell transistor for the next generation DRAM architecture because of its low leakage current, high mobility, and the back-end-of-line (BEOL) compatibility that enables monolithic 3D (M3D) integration. IGZO-based electronic devices used in harsh environments such as radiation exposure can be vulnerable, resulting in functional failure. Here, the behavior of subgap density-of-states (DOS) over full subgap range according to the impactful gamma-ray irradiation in a-IGZO TFTs is investigated by employing DC current–voltage (I−V) data with multiple-wavelength light sources. To understand the origins of the radiation effect, IGZO films have been also analyzed by x-ray photoelectron spectroscopy (XPS). Considering in-depth electrical and chemical analysis, the unexpected increase of subthreshold leakage current caused by total ionizing dose (TID) is strongly correlated with newly discovered deep-donor states ((Formula presented.)) at the specific energy level. In particular, oxygen vacancies caused by the gamma-ray irradiation give rise to undesirable electrical characteristics such as hysteresis effect and negative shift of threshold voltage (VT). Furthermore, the TCAD simulation results based on DOS model parameters are found to exhibit good agreement with experimental data and plausible explanation including ((Formula presented.)).
Keywords: Amorphous InGaZnO; Amorphous oxide semiconductors; C. thin film transistor (TFT); Cell transistor; Densities of state; Direct observations; Gamma rays irradiation; Multiple wavelengths; Multiple-wavelength light source; Subgap density-of-state; amorphous oxide semiconductor; gamma-ray irradiation; indium gallium zinc oxide; multiple-wavelength light source; subgap density-of-states